2013
DOI: 10.1136/vr.101530
|View full text |Cite
|
Sign up to set email alerts
|

A spectral‐domain optical coherence tomography device provides reliable corneal pachymetry measurements in canine eyes

Abstract: The objective of this study was to determine central corneal thickness (CCT) and the intra- and interuser reliability using a portable spectral-domain optical coherence tomography (SD-OCT) device in canine eyes. Twenty clinically normal dogs were examined. CCT measurements were obtained from both eyes of each animal three times by two operators in succession. The CCT was automatically calculated using the pachymetry software generated from eight radial scans, 6 mm in length. Mean canine CCT was 606.83±39.45 μm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 21 publications
2
28
0
Order By: Relevance
“…Another group of studies has shown the lack of difference of the OCT when compared to the Scheimpflug camera ultrasound pachymetry and optical low‐coherence reflectometry . Independent of those comparisons, SD‐OCT has shown high reliability in obtaining corneal measurements in the human, canine, feline, and equine species …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another group of studies has shown the lack of difference of the OCT when compared to the Scheimpflug camera ultrasound pachymetry and optical low‐coherence reflectometry . Independent of those comparisons, SD‐OCT has shown high reliability in obtaining corneal measurements in the human, canine, feline, and equine species …”
Section: Discussionmentioning
confidence: 99%
“…In the veterinary ophthalmic literature, the use of OCT was first reported in 2007 in a study evaluating retinal structure in the cat and in 2008 to describe the retinopathy of the Coton de Tulear dogs . Recently, several studies have used OCT to characterize the normal cornea, iridocorneal angle, and retina in several species, as well as corneal abnormalities in dogs and cats . In the majority of these studies, the animals were under general anesthesia or deep sedation to avoid eye movement during imaging …”
Section: Introductionmentioning
confidence: 99%
“…Fourier‐domain OCT (FD‐OCT) has also been used for diagnosing and monitoring other anterior segment conditions such as conjunctivochalasis and been used for assessing the tear meniscus of humans . In veterinary ophthalmology, OCT has been primarily used in canine retinal and glaucoma research and there are currently limited data available on OCT values of the canine anterior segment . Studies have found SD‐OCT to be a reliable tool for measuring CCT in dogs …”
Section: Introductionmentioning
confidence: 99%
“…In veterinary ophthalmology, OCT has been primarily used in canine retinal and glaucoma research and there are currently limited data available on OCT values of the canine anterior segment . Studies have found SD‐OCT to be a reliable tool for measuring CCT in dogs …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation